Measurements of the transverse-momentum-dependent cross sections of J /ψ production at mid-rapidity in proton+proton collisions at s =510 and 500 GeV with the STAR detector - STAR Collaboration (Physical Review D, 2019)
We present measurements of the differential cross sections of inclusive J/ψ meson production as a function of transverse momentum (pTJ/ψ) using the μ+μ- and e+e- decay channels in proton+proton collisions at center-of-mass energies of 510 and 500 GeV, respectively, recorded by the STAR detector at the Relativistic Heavy Ion Collider. The measurement from the μ+μ- channel is for 0<pTJ/ψ<9 GeV/c and rapidity range |yJ/ψ|<0.4, and that from the e+e- channel is for 4<pTJ/ψ<20 GeV/c and |yJ/ψ|<1.0. The ψ(2S) to J/ψ ratio is also measured for 4<pTmeson<12 GeV/c through the e+e- decay channel. Model calculations, which incorporate different approaches toward the J/ψ production mechanism, are compared with experimental results and show reasonable agreement within uncertainties. © 2019 authors. Published by the American Physical Society.
8 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed